2022
DOI: 10.1097/jte.0000000000000241
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of On-Site Visits From the Physical Therapy Clinical Instructor Perspective: A Mixed-Methods Approach

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Palmer and Rapport 5 found that in-person site visits strengthened the relationship between the site and school. This relationship is an important factor to consider because the Clinical Education Placement Process Task Force recommended strengthening bonds between the school and the clinical site to maximize the effectiveness of clinical education.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Palmer and Rapport 5 found that in-person site visits strengthened the relationship between the site and school. This relationship is an important factor to consider because the Clinical Education Placement Process Task Force recommended strengthening bonds between the school and the clinical site to maximize the effectiveness of clinical education.…”
Section: Discussionmentioning
confidence: 99%
“…If a student is struggling in the clinic or a site is new, and a relationship needs to be established, an in-person visit may be time and cost-effective, given what can be gained by the in-person interaction. [3][4][5] In-person visits allow the faculty to see how the student interacts not only with the CI but also with other staff members and, possibly, patients. In addition, the faculty visitor can gauge the clinic's environment more easily than by phone or video.…”
Section: Implications For Practicementioning
confidence: 99%
See 3 more Smart Citations